Diagnosis and treatment of pediatric myelodysplastic syndromes: A survey of the North American Pediatric Aplastic Anemia Consortium. Issue 10 (11th August 2020) - Nakano, Taizo A.; Lau, Bonnie W.; Dickerson, Kathryn E.; Wlodarski, Marcin; Pollard, Jessica; Shimamura, Akiko; Hofmann, Inga; Sasa, Ghadir; Elghetany, Tarek; Cada, Michaela; Dror, Yigal; Ding, Hilda; et al.
Abstract: Background: Myelodysplastic syndromes (MDS) represent a group of clonal hematopoietic stem cell disorders that commonly progress to acute myeloid leukemia (AML). The diagnostics, prognostics, and treatment of adult MDS are established but do not directly translate to children and adolescents. Pediatric MDS is a rare disease, characterized by unique cytogenetics and histology compared with adult MDS, and often arises secondary to germline predisposition or cytotoxic exposures. Our objective was to highlight aspects of diagnosis/management that would benefit from further systematic review toward the development of clinical practice guidelines for pediatric MDS. Procedure: The North American Pediatric Aplastic Anemia Consortium (NAPAAC) is composed of collaborative institutions with a strong interest in pediatric bone marrow failure syndromes and hematologic malignancies. The NAPAAC MDS working group developed a national survey distributed to 35 NAPAAC institutions to assess data on (1) clinical presentation of pediatric MDS, (2) diagnostic evaluation, (3) criteria for diagnosis, (4) supportive care and treatment decisions, and (5) role of hematopoietic stem cell transplantation (HSCT). Results: Twenty‐eight of 35 institutions returned the survey. Most centers agreed on a common diagnostic workup, though there was considerable variation regarding the criteria for diagnosis. Although there was consensus on supportive care, treatment strategies, including the role of cytoreduction and HSCT, varied across centers surveyed. Conclusions: There is lack of national consensus on diagnosis and treatment of pediatric MDS. This survey identified key aspects of MDS management that will warrant systematic review toward the goal of developing national clinical practice guidelines for pediatric MDS.